TINGKAT STRES DAN INDEKS MASSA TUBUH TERHADAP TEKANAN DARAH MAHASISWA - Made Ermayani (Jurnal Keperawatan Dirgahayu (JKD), 2021)
Hypertension is a disease that can occur from a young age. Students who are in the young adult age group with an unhealthy lifestyle are prone to severe hypertension. Many risk factors for hypertension include stress levels and body mass index (BMI). Knowing that matters related to blood pressure can be used as a preventive measure to prevent complications of hypertension. This study was to determine the relationship between stress levels and body mass index with blood pressure in students of STIKES Dirgahayu Samarinda. This quantitative research was a correlation analytic study with a cross sectional study design. Purposive sampling was used for sampling method, and as an analysis, researcher used the Spearman rho test and multiple correlation test. Respondents aged 17-25 years, mostly female (82%), low socioeconomic level (47.1%), non-smokers (86.8%), exercising at least once / month (50.3%), and have a family history of hypertension (54.5%). The majority of respondents' stress levels were included in moderate anxiety (58.2%), with normal BMI values (69.3%), normal systolic blood pressure (61.9%) and normal diastolic blood pressure (48.1%). Stress level and body mass index are simultaneously related to blood pressure, both systolic blood pressure and diastolic blood pressure, with a p value of 0.000 <0.05. There is a relationship between stress levels and body mass index with the blood pressure of STIKES Dirgahayu Samarinda students.